When Death Enters the Theater of Psychodrama: Perspectives and Strategies of Psychodramatists. Issue 5 (18th August 2019) - Testoni, Ines; Cichellero, Silvia; Kirk, Kate; Cappelletti, Virginia; Cecchini, Clara
Abstract: Death is the most threatening experience to human life because it is inevitable and causes irreversible loss. The article describes the results of a qualitative study undertaken with 25 Italian psychodramatists. Respecting the Consolidated Criteria for Reporting Qualitive Research (COREQ) checklist, the research was aimed at bringing out their strategies and techniques used to manage loss and grief when real or symbolic death appeared in patients' narratives. The results showed that participants overwhelmingly believed that psychodrama offers excellent instruments to treat both forms of grief, despite few differences between the forms having been recognized. The participants considered the main strategies to be the therapeutic action of the group and the surplus-reality to put on a scene of death and the dead, while the main techniques are the role reversal involving the representation of the lost person or situation with the auxiliary ego, the empty chair, the double, and the genodrama. Finally, a striking factor from the qualitative analysis was that it diagnosed a lack of competence related to an explanation of real grief and its complex constellation. Suggestions useful for the improvement of psychodrama in the treatment of all types of loss are presented. Particular attention is paid to the continuing bonds.